Beyond the Chatbot: Conceptualizing Prompt Literacy as a Core Dimension of AI Literacy in EFL Writing Pedagogy - Patty, Jusak (Journal of Education Method and Learning Strategy, 2026)
Generative AI tools have introduced literacy demands in English as a Foreign Language (EFL) writing instruction that existing frameworks do not fully address. This narrative review synthesizes empirical and theoretical studies published between 2020 and 2025 to examine prompt literacy as a core dimension of AI literacy in EFL writing pedagogy. Drawing primarily on research from Asian EFL contexts, the review pursues three objectives: conceptualizing prompt literacy, examining the linguistic and cognitive challenges EFL learners encounter when formulating prompts, and identifying pedagogical approaches to integrate prompt literacy into writing instruction. Analysis across the reviewed literature indicates that effective prompting requires linguistic precision, rhetorical awareness, and metacognitive monitoring rather than technical procedures alone. Current AI literacy frameworks offer limited guidance on text-based interaction with generative systems. Language proficiency shapes prompting practices: lower-proficiency learners rely on generic requests, while higher-proficiency learners engage in strategic refinement. Cognitive load from simultaneous language formulation and AI interaction may constrain performance, though metacognitive support mitigates these effects. Four pedagogical dimensions emerge: systematic instructional frameworks, iterative interaction patterns, teacher professional development requirements, and assessment approaches addressing both processes and products. The review argues that prompt literacy functions as a foundational competency for effective AI-mediated composition in EFL contexts.